Interactions between common vole and winter rape. Issue 2 (4th September 2020) - Heroldová, Marta; Šipoš, Jan; Suchomel, Josef; Zejda, Jan
Abstract: Winter rape is a widespread crop in Europe that provides the common vole with a suitable diet and cover from autumn to late spring (approximately 8 months). This review shows the following: That common vole populations reach a high density in winter rape. Widespread rape fields (large size) provide better support for common vole populations compared to winter cereals. That a high‐quality supply from winter rape enables the common vole to extend its reproductive season and successfully overwinter. That the diet of the common vole primarily comprises the green vegetative parts of winter rape. The percentage of weed species in the diet depends on weed coverage in the crop. That the impact of the common vole on winter rape correlates with vole density. That no‐tillage farming enhances common vole infestation of winter rape fields, particularly in spring, and is related to damage to adjacent crops. © 2020 Society of Chemical Industry Abstract : Winter rape, as widespread crop in Europe, provides common vole with a suitable diet and cover from autumn to spring. In summer are voles forced to migrate to other crops.